CSF Cytokines in Aging, Multiple Sclerosis, and Dementia - Hu, William T.; Howell, Jennifer Christina; Ozturk, Tugba; Gangishetti, Umesh; Kollhoff, Alexander L.; Hatcher-Martin, Jaime M.; Anderson, Albert M.; Tyor, William R. (Frontiers in Immunology, 2019)
Inflammation is a common process involved in aging, multiple sclerosis (MS), and age-related neurodegenerative disorders such as Alzheimer’s disease (AD) and Parkinson’s disease (PD), but there is limited evidence for the effects of aging on inflammation in the central nervous system. We collected cerebrospinal fluid (CSF) from 105 healthy control subjects representing a wide age range (23-86), and analyzed levels of cytokines associated innate immunity (TNF-alpha) and different T-helper subtypes: interferon –gamma induced protein 10 (IP-10) for Th1, interleukin-10 (IL-10) for Th2, and interleukin 8 (IL-8/CXCL8) for Th17. We show that CSF levels of TNF-alpha, IP-10, and IL-8 all increased linearly with age, but levels of IL-10 demonstrated a U-shaped relationship with age. We further found greater age-related increases in TNF-alpha, IL-10, and IL-8 relative to increases in IP-10 levels, consistent with a shift from Th1 to other inflammatory phenotypes. Finally, when we analyzed the same four cytokines in people with neurological disorders, we found that MS and AD, but not PD or dementia with Lewy bodies, further accentuated the age-related shift from Th1- to non-Th1-related cytokines. We propose that CSF cytokine levels represent powerful surrogates of brain inflammation and aging, and some, but not all, neurological disorders accelerate the shift away from Th1 phenotypes.